1999
DOI: 10.1159/000013418
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Parameters, Nutritional Status and Efficiency of Dialysis in CAPD and CCPD Patients

Abstract: Background/Aims: Several studies indicate that small solute transport is influenced by peritoneal dialysate volume and dwell time. This study focuses on the clinical impact of peritoneal dialysis modality, continuous ambulatory peritoneal dialysis (CAPD) and continuous cycling peritoneal dialysis (CCPD). Methods: We studied 18 patients on CAPD and 11 on CCPD for 18 months and assessed biochemical parameters, nutritional status and efficiency of dialysis at 6-month intervals. Results: Four-hour D/P urea and cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Given that peritoneal dialysate is potassium-free, ongoing losses of potassium into dialysate may contribute to hypokalemia in some patients. Our results were in accordance with previous studies [24], [25], revealing that an elevated dialysis dose was independently related to decreased serum potassium levels. In addition, potassium redistribution into the intracellular compartment, stimulated by insulin release due to continuous peritoneal glucose infusion was thought to be another important risk factor for hypokalemia [23].…”
Section: Discussionsupporting
confidence: 94%
“…Given that peritoneal dialysate is potassium-free, ongoing losses of potassium into dialysate may contribute to hypokalemia in some patients. Our results were in accordance with previous studies [24], [25], revealing that an elevated dialysis dose was independently related to decreased serum potassium levels. In addition, potassium redistribution into the intracellular compartment, stimulated by insulin release due to continuous peritoneal glucose infusion was thought to be another important risk factor for hypokalemia [23].…”
Section: Discussionsupporting
confidence: 94%
“…Some investigators [10] observed that high-dose CCPD is better than CAPD concerning ultrafiltration and urea clearances, while others [11][12][13] could not demonstrate statistically significant differences in the weekly urea Kt/V and creatinine clearance between CAPD and APD patients. Our study did not find any difference in adequacy parameters in terms of small-solute clearances between groups, but net ultrafiltration and peritoneal sodium removal were higher in our CAPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since CCPD uses a greater number of exchanges with shorter dwell times and does not allow for equilibration to occur, there is always a concentration gradient difference between the dialysate and the plasma allowing more potassium to be transported into the dialysate fluid. It has also been shown that patients treated with CCPD tend to have more gastrointestinal symptoms, which may result in a decreased potassium intake [21].…”
Section: Peritoneal Dialysismentioning
confidence: 99%